Creating mosaics: the interrelationships of knowledge and context. - Daley BJ (Journal of Continuing Education in Nursing)
This qualitative interpretivist study analyzed the interrelationships between the knowledge gained through continuing nursing education programs and the context of nurses' clinical practice. The content of nursing continuing education programs offered 9-12 months previously was reviewed. Forty semi-structured, tape-recorded interviews were conducted with nurses from hospitals, nursing homes and home care agencies to determine their use of this new knowledge. Findings indicate that nurses used information from continuing education programs to construct a knowledge base and that this process was affected by the structural, human resources, political and symbolic frames of the context in which nurses practice.